Evaluasi Layout Fasilitas Produksi Minyak Kelapa Sawit di PT.ABC dengan Metode Activity Relationship Chart (ARC) dan Activity Relationship Diagram (ARD) - Halimsyah, Halimsyah; Syara Nasution, Rivara; Nugroho, Handi Wilujeng (Greeners: Journal of Green Engineering for Sustainability, 2023)
The success of an industry is a positive impact of integrating production factors andmanagement systems to be more effective and efficient. One of the determinants of anindustry's success is the layout, better known as the layout of the industry. Knowledge of theseincludes work centres and equipment in the conversion process to optimize the relationshipbetween implementing officers, material flow, information flow, and procedures for achievinggoals. ABC company is one of the companies engaged in the processing of oil palm fruit toproduce various kinds of products that are useful for human food, beverages, agriculture,industry, and so on. This study evaluates the layout of PT. ABC's production facilities,utilizing an activity relationship chart and activity relationship diagram approach. Researchersanalyzed the data and obtained two factory facility layout designs, the 1st and 2ndalternatives, ultimately selecting the latter. The chosen layout design is more organized andsupports the smooth running of production activities, providing significant advantages for thecompany.